Efficacy of Hematopoietic Stem Cell Transplantation with CCR5Δ32 Homozygous Donors in Achieving Sustained HIV-1 Remission: A Systematic Literature Review - Paishal Mizan; Raveinal; Dwitya Elvira (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: The pursuit of a cure for Human Immunodeficiency Virus type 1 (HIV-1) infection has led to the exploration of innovative therapeutic strategies. Hematopoietic stem cell transplantation (HSCT) from donors homozygous for the CCR5Δ32 mutation, which confers resistance to HIV-1 infection, has emerged as a promising approach following the notable cases. This study aimed to evaluate the efficacy of HSCT with CCR5Δ32 homozygous donors in achieving sustained HIV-1 remission. Methods: A systematic search of major electronic databases, including PubMed, Scopus, and Web of Science, was conducted for studies published between 2013 and 2024 that reported on the outcomes of HIV-1 positive individuals who underwent HSCT with CCR5Δ32 homozygous donors. The primary outcome of interest was sustained HIV-1 remission, defined as the absence of detectable viral load in the absence of antiretroviral therapy (ART) for a period of at least 12 months post-transplantation. Data on patient characteristics, transplantation procedures, conditioning regimens, graft-versus-host disease (GVHD), and duration of remission were extracted and synthesized. Results: Five case studies met the inclusion criteria. These studies predominantly involved individuals with advanced HIV-1 infection who also had hematological malignancies necessitating HSCT. All patients received allogeneic HSCT from donors with the CCR5Δ32/Δ32 genotype. Conditioning regimens varied but generally included chemotherapy with or without total body irradiation. Graft-versus-host disease was a common complication, ranging from mild to severe. Sustained HIV-1 remission, defined by the interruption of ART with undetectable viral load, was achieved in most reported cases for varying durations. Data, based on the patterns observed in these five cases, suggested that approximately 60-80% of patients receiving HSCT from CCR5Δ32 homozygous donors might achieve at least 12 months of ART-free HIV-1 remission, with a smaller subset achieving long-term remission beyond 5 years. Conclusion: HSCT with CCR5Δ32 homozygous donors demonstrated a significant potential for achieving sustained HIV-1 remission in a select group of individuals, primarily those with hematological malignancies.